Gender and conflict embodiments, discourses and symbolic practices - Frerks, Georg, 1954-; Ypeij, Johanna Louisa; Konig, Reinhilde Sotiria (Gender in a global/local world., 2014)
Through an in-depth analysis of the multifaceted manifestations of gender and conflict, this book shows how cognition and behaviour, agency and victimization, are gendered beyond the popular stereotypes. Conflict not only reconfirms social hierarchies and power relations, but also motivates people to transgress cultural boundaries and redefine their self-images and identities. The contributions are a mix of classical ethnography, performance studies and embodiment studies, showing 'emotions and feelings' often denied in scientific social research.